2020
DOI: 10.1177/1524839920968523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Pandemic on the Professional Roles and Responsibilities of Health Educators

Abstract: Public health professionals are at the forefront of the COVID-19 pandemic response. However, the roles and responsibilities of health educators in pandemic response are unknown. Researchers examined multiple factors that described how health educators’ work priorities and lives have been affected by COVID-19. An electronic questionnaire was administered nationally to health educators to assess the effect of the pandemic on their professional responsibilities, the challenges they are facing, and their fears abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 6 publications
1
18
0
1
Order By: Relevance
“…New technology in the fourth industrial revolution might influence the types of job tasks required of individuals, which health professionals during the current pandemic have experienced [ 140 ]. Thus, we tried to include task-related factors (specialty, manager’s concern) in the alternative expanded model.…”
Section: Resultsmentioning
confidence: 99%
“…New technology in the fourth industrial revolution might influence the types of job tasks required of individuals, which health professionals during the current pandemic have experienced [ 140 ]. Thus, we tried to include task-related factors (specialty, manager’s concern) in the alternative expanded model.…”
Section: Resultsmentioning
confidence: 99%
“…Fourth, our survey also did not capture any information about the personal or mental health effects of COVID-19 on patient educators, especially during the rapid transition to remote work where some may have felt isolated and unable to interact with colleagues, friends, and family or were required to take on the additional role of overseeing online school for children [ 27 ]. A previous study examining the effects of the COVID-19 pandemic on health educators reported that in addition to increased job responsibilities, health educators took on a greater role in caring for family members and helping children with online school [ 5 ]. These conditions are likely to lead to burnout and elevated stress over time, if they have not already [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…When a person receives a cancer diagnosis, education is vital in reducing anxiety [ 1 ], increasing satisfaction with treatment [ 2 ], helping with self-management [ 3 ], and creating a sense of control [ 4 ]. When the COVID-19 pandemic became a reality in the spring of 2020, many patient education programs in Canada and the USA suddenly found themselves closing their physical spaces; moving their staff to remote work; and, in some cases, redeploying their staff to COVID-19-related roles [ 5 ]. However, COVID-19 did not stop the education needs of people with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…As investigações já realizadas sobre o impacto da pandemia nos profissionais de saúde reforçaram este resultado (Borges et al, 2021;Jin et al, 2020). Inevitavelmente houve a necessidade dos serviços se organizarem e redefinirem prioridades em função da pandemia (Hancher-Rauch et al, 2021) o que se refletiu em todas as áreas da vida destes profissionais. Além destas mudanças, o facto destes profissionais estarem mais expostos ao vírus gerava um stress adicional no momento de prestação de cuidados (Teixeira et al, 2020).…”
Section: Discussionunclassified